Community Socioeconomic Deprivation and Nonalcoholic Fatty Liver Disease Severity. Issue 3 (March 2020) - Orkin, Sarah; Brokamp, Cole; Yodoshi, Toshifumi; Trout, Andrew T.; Liu, Chunyan; Meryum, Syeda; Taylor, Stuart; Wolfe, Christopher; Sheridan, Rachel; Seth, Aradhna; Bhuiyan, Mohammad Alfrad Nobel; Ley, Sanita; et al.
ABSTRACT: Background and Objectives: Nonalcoholic fatty liver disease (NAFLD) is linked to obesity. Obesity is associated with lower socioeconomic status (SES). An independent link between pediatric NAFLD and SES has not been elucidated. The objective of this study was to evaluate the distribution of socioeconomic deprivation, measured using an area-level proxy, in pediatric patients with known NAFLD and to determine whether deprivation is associated with liver disease severity. Methods: Retrospective study of patients <21 years with NAFLD, followed from 2009 to 2018. The patients' addresses were mapped to census tracts, which were then linked to the community deprivation index (CDI; range 0--1, higher values indicating higher deprivation, calculated from six SES-related variables available publicly in US Census databases). Results: Two cohorts were evaluated; 1 with MRI (magnetic resonance imaging) and/or MRE (magnetic resonance elastography) findings indicative of NAFLD (n = 334), and another with biopsy-confirmed NAFLD (n = 245). In the MRI and histology cohorts, the majority were boys (66%), non-Hispanic (77%–78%), severely obese (79%–80%), and publicly insured (55%–56%, respectively). The median CDI for both groups was 0.36 (range 0.15–0.85). In both cohorts, patients living above the median CDI were more likely to be younger at initial presentation, time of MRI, and time of liver biopsy. MRI-measured fat fraction and liver stiffness, as well as histologic characteristics were not different between the high- and low-deprivation groups. Conclusions: Children with NAFLD were found across the spectrum of deprivation. Although children from more deprived neighborhoods present at a younger age, they exhibit the same degree of NAFLD severity as their peers from less deprived areas. Abstract : Supplemental Digital Content is available in the text